FIZZLEBERT STUMP : AND THE BEARDED BOY - Harrold, A.F., 1975-; Horne, Sarah (London : Bloomsbury, 2013)
The bearded Barboozul family are the new stars of Fizz's circus. Their act is full of magic, mystery, fear and fun. But then things start going wrong. The lion loses his dentures. The clowns lose their noses. The Ringmaster loses his temper. And the circus is about to lose its licence.
Fizzlebert Stump Collection 3 Children Books Set by A.F. Harrold Titles in the Set are Fizzlebert Stump: The Boy Who Cried Fish, Fizzlebert Stump and the Bearded Boy, Fizzlebert Stump: The Boy Who Ran Away From the Circus (and joined the library).
Keywords: Children's stories, English; English fiction